Kinerja Badan Pendapatan Daerah dalam Optimalisasi Sumber-Sumber Pendapatan Asli Daerah di Kota Jayapura - Sangquan Uchi Waromi (Institut Pemerintahan Dalam Negeri (IPDN), 2021)
This research discusses the performance of regional revenue agencies in optimizing sources of local revenue in Jayapura City. The purpose of this research is to observe and find out the stipulations or conditions of achievement that are determined to measure the performance of the Jayapura City Regional Income Agency, in order to determine the factors that support and hinder the performance of the Jayapura City Regional Income Agency. The research method used is descriptive research with an inductive approach. In collecting data, the writer uses interview, observation, and documentation techniques. Data analysis in this study includes data reduction, data presentation, and conclusion drawing. The results show how the performance of the local revenue agency in the city of Jayapura in optimizing the sources of local revenue, the factors that support and hinder it internally and externally, and the efforts made by the regional revenue agency to overcome various hindering factors.